НАСЛЕДУЕМОСТЬ СЕЛЕКЦИОНИРУЕМЫХ ПРИЗНАКОВ ОВЕЦ ПОРОДЫ КАЗАХСКИЙ АРХАРОМЕРИНОС (Experimental biology, 2009)
It is considered questions of heritability of economic-useful attributes of sheeps of breed Kazakh archarmerinos.
Keywords: Kazakh archarmerinos